Women and the discourse of marriage: A critical analysis of Jane Eyre and Pride and Prejudice - Diniz, Gabriely Cristina Queiroga (Open Science Journal, 2020)
This short article aims to compare the discourse of the characters Jane Eyre from the eponymous novel by Charlotte Brontë, and Elizabeth Bennet from Pride and Prejudice by Jane austen, in which both of them refuse marriage proposals. As criteria of comparison its pointed: i) the reasons why they decided to decline the proposals, ii) the way they express their emotions during the moments, iii) the reactions of the male characters after the women’s answers.